Multicultural education as a reform initiative: reconstructing teacher preparation for Malaysian ``Vision Schools'' - Malakolunthu, S.; Siraj, Saedah; Rengasamy, N.C. (De La Salle Univ-Manila, 2010)
This article reports a case study of three ``Vision Schools'' in Malaysia. The Vision Schools house the Malay, Mandarin, and Tamil vernacular primary schools in the same compound, which allow their members to share space and facilities, and jointly organize school events. These have been constructed to promote cultural awareness, co-existence, and cooperation among the students of different racial and ethnic groups by creating opportunities for them to come together and mingle, learn about one another's way of life, and become culturally tolerant and informed. The key players in the promotion of the ideals of the Vision Schools are the teachers who, however, have not been able to bring forth their contribution. The study reveals that they have to have a multicultural mind-set and conceptual understanding of multiculturalism. They also have to be pedagogically proficient and be provided with a proper curricular structure and content in multicultural education. It is imperative that these aspects are incorporated in teacher development programs for successful implementation of multiculturalism.